1982
DOI: 10.1136/bmj.284.6316.632
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation side and occurrence of mittelschmerz in spontaneous and induced ovarian cycles.

Abstract: is nephrotoxic when included in analgesic mixtures or given to patients with pre-existing analgesic nephropathy. Nevertheless, they give reassuring evidence that aspirin used as sole treatment for rheumatoid arthritis over many years in standard therapeutic dosage carries little or no risk of renal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 6 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…The same considerations apply to the theory suggesting that large endometriomas may develop as a result of secondary invasion of luteal cysts by ovarian surface endometriotic cells 14 . In fact, according to the available evidence, ovulation occurs either equally on both sides 15 or more frequently on the right 16 but not the left side. If instead retrograde menstruation is the origin of endometriotic lesions 2,3,17 our findings should be considered taking into account anatomic factors that may influence the distribution and implantation of regurgitated endometrial cells 4,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The same considerations apply to the theory suggesting that large endometriomas may develop as a result of secondary invasion of luteal cysts by ovarian surface endometriotic cells 14 . In fact, according to the available evidence, ovulation occurs either equally on both sides 15 or more frequently on the right 16 but not the left side. If instead retrograde menstruation is the origin of endometriotic lesions 2,3,17 our findings should be considered taking into account anatomic factors that may influence the distribution and implantation of regurgitated endometrial cells 4,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…By adding 0.31 to 14.13 a value of 14.44 days is obtained which agrees closely with the geometric mean luteal phase length (14.3 days) calculated using the parameter intermenstrual pain (Vollman 1977). This suggests that intermenstrual pain may well be associated with actual event of ovulation ( H a m et al 1979;Marinho et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…A chronological order of ovulations was then calculated which suggested that ovulation occurred in a turn-about manner. Other studies in the human (Marinho et al, 1982) and non-human primate (Dukelow, 1977;Hodgen, 1982) also implicate contralateral ovulation. In contrast, Werlin et al (1986) suggest that ipsilateral ovulations are the norm in women.…”
Section: Endocrine Action Between Ovariesmentioning
confidence: 99%